A professional foreigner : life in diplomacy - Marks, Edward, 1934- (ADST-DACOR diplomats and diplomacy series., 2023)
"A Professional Foreigner aims to provide insight into the profession itself, what it was like at a particular period of history to play even a minor role in the steady stream of history, in the more mundane world of daily events, often out of the view of the media and world attention. It portrays a workday American professional diplomat - a Foreign Service officer - what they think and what they do all day"--